POTENTIAL RESOURCES IN CONSERVATION UNIVERSITY FOR GREEN INFRASTRUCTURE DEVELOPMENT - Indrianingrum, Lulut (Jurnal Teknik Sipil dan Perencanaan, 2014)
Semarang State University (UNNES) as part of a larger community has initiated the positive development for the surrounding environment by establishing itself as a conservation university. The university has many potentials resources that can be developed into initial model of Green Infrastructure in university scale. This paper aims to present the supports, burdens and limitations of GI implementation in the universityâs area through identifying resources that university have. Supports of the university include natural resources, man-made resources, institution and programs. Burdens and limitations explain the challenge for the university to implement and securing GI as an ongoing commitment and goal. Methodology used is primary observation and documents analysis. The analysis shows that the application of GI in the university is very possible regarding its natural and man-made resource supports as well as institutional and the university programs. Natural Resources supports are through the existence of birds and butterflies in the area of UNNES and some of them are classified as endangered species. The university is located among two kinds of important natural landscapes; there is valley with dense vegetation and river banks with steep cliffs. Those landscapes are potential for GI in UNNES. Man Made resources include water conservation zone, biodiversity conservation facilities and green spaces inside the campus. Supports from institution and programs are abundant because the vision of UNNES as a conservation university. GI in UNNES should include natural landscapes outside the area of campus to make a possible connection to create network required for GI system.Â